[1990] Proceedings of the 2nd International IEEE Conference on Tools for Artificial Intelligence
DOI: 10.1109/tai.1990.130405
|View full text |Cite
|
Sign up to set email alerts
|

Software representation to support change

Abstract: Research methodology, from cognitive science and artificial intelligence, is applied to theproblem of software representation to support the process of software change. A model of software to support change, suggested by thecurrentresearch, ispresented. Populating that model requires data from tasks related to codebased functional decomposition, data abstraction and functional data flows. A competence model for the task of code-based functional decomposition is proposed. The Problem of Software ChangeSoftware … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…To understand software, a functionality model is needed. This functionality model must be tightly coupled with the code (S. Chen et al, 1990Chen et al, , 1992Heisler, 1993;Huang et al, 1995) as the user's main aim is to understand the code. There should be traceability between the functionality model and the code.…”
Section: Research Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand software, a functionality model is needed. This functionality model must be tightly coupled with the code (S. Chen et al, 1990Chen et al, , 1992Heisler, 1993;Huang et al, 1995) as the user's main aim is to understand the code. There should be traceability between the functionality model and the code.…”
Section: Research Topicsmentioning
confidence: 99%
“…There should be traceability between the functionality model and the code. Functionality should be attached to the various control constructs (Heisler, 1993;Heisler et af., 1993) and the data (Joiner et af., 1994; X. P. Chen et al, 1994a) found in the programs. HSK emphasize program understanding by Japanese annotation and various reverse-engineering models.…”
Section: Research Topicsmentioning
confidence: 99%